Asertivitas pada Perempuan Korban Kekerasan dalam Pacaran Ditinjau dari Tipe Kepribadian - Zahara Anindya Suryana Putri; Adelina Rahmawati (Program Studi Bimbingan dan Konseling FKIP UMSU, 2026)
Dating violence remains a significant issue among young women and may have adverse psychological consequences, including reduced assertiveness. Assertiveness is considered an important personal skill that enables individuals to express their thoughts, feelings, and boundaries effectively, thereby reducing vulnerability to unhealthy relationships. This study aimed to examine the relationship between personality type (extrovert–introvert) and assertiveness among young adult women who have experienced dating violence. A quantitative correlational design was employed involving 228 female participants aged 18–25 years who met the research criteria. Participants were selected using purposive sampling. Personality type was measured using the Eysenck Personality Inventory (EPI), while assertiveness was assessed using an assertiveness scale adapted from Alberti and Emmons. Data were analyzed using descriptive statistics, Pearson Product-Moment correlation, and independent sample t-test. The results showed a positive but weak relationship between personality type and assertiveness (r = 0.124, p 0.05), indicating that the relationship was not statistically significant. Furthermore, no significant difference in assertiveness levels was found between extrovert and introvert participants (t = 0.631, p = 0.529). These findings suggest that personality type is not a determining factor of assertiveness among women who have experienced dating violence. Other psychological factors, such as self-esteem and the impact of violence experiences, may play a more substantial role in shaping assertive behavior. Future studies are recommended to explore additional factors influencing assertiveness among victims of dating violence using broader and more diverse samples.